1997
DOI: 10.1038/ki.1997.115
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage analysis of growth factor loci and end-stage renal disease in African Americans

Abstract: Hypertension, diabetes mellitus and chronic glomerular diseases reportedly cause in excess of 80% of the incident cases of end-stage renal disease (ESRD) in the U.S. The factors that initiate progressive renal failure in patients with these disorders remain unknown. Several investigators have reported enhanced synthesis and activity of cytokines in the kidneys of patients with renal failure. The ensuing inflammation and fibrosis have been postulated to contribute to the development of progressive renal failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 28 publications
1
46
0
Order By: Relevance
“…Recruitment of African-American and EuropeanAmerican patients and control subjects has previously been described (16). Briefly, 577 unrelated African-American patients with type 2 diabetes, born in North Carolina, South Carolina, Georgia, Tennessee, or Virginia, were recruited from dialysis facilities.…”
Section: Methodsmentioning
confidence: 99%
“…Recruitment of African-American and EuropeanAmerican patients and control subjects has previously been described (16). Briefly, 577 unrelated African-American patients with type 2 diabetes, born in North Carolina, South Carolina, Georgia, Tennessee, or Virginia, were recruited from dialysis facilities.…”
Section: Methodsmentioning
confidence: 99%
“…DNA samples were collected from self-described African American families with multiple T2DM-affected members. Recruitment strategies and selection criteria have been described in detail previously (Yu et al 1996(Yu et al , 1998(Yu et al , 2000Freedman et al 1997Freedman et al , 2000Freedman et al , 2002. Briefly, families were originally identified through a proband with impaired renal function, either with end-stage renal disease (ESRD) and on dialysis, or nephropathy (defined as urinalysis with ≥ 100 mg/dl protein, urine albumin:creatinine ratio (ACR) ≥ 0.50 g/g, and/or serum creatinine concentration >1.5 mg/dl), associated with T2DM.…”
Section: Selection Criteria and Recruitmentmentioning
confidence: 99%
“…The VNTR polymorphism located in the third intron consists of three 70-bp repeats, with two repeats and four repeats of rare alleles, which are the candidate genes for this disease (Kirchheiner et al, 2006;Mittal and Manchanda, 2007;Konwar and Bid, 2008). Many studies have reported that gene polymorphism of IL-4 is associated with ESRD (Freedman et al, 1997;Nordfors et al, 2005;Wetmore et al, 2005).…”
Section: Introductionmentioning
confidence: 99%